Cattle microsatellite markers successfully established diversity status of Arunachali yak (only registered yak breed of India) - SHARMA, HIMANI; SHARMA, REKHA; AHLAWAT, SONIKA; DAS, P J; JAYAKUMAR, S; TANTIA, M S (The Indian Journal of Animal Sciences, 2018)
Yak diversity of the country has remained predominantly unexplored for a long time. Among the 169 registered livestock breeds of India, the sole representation from yak genetic resources is the Arunachali yak. This study for the first time investigated genetic diversity status of Arunachali yak using 26 bovine microsatellite markers. All the markers recommended for cattle except one (ILSTS05) amplified with yak genome. Allelic genotype pattern overlapped between yak and cattle across 25 microsatellite loci and a total of 233 alleles were detected in yak. The number of observed alleles across loci ranged from 3–16 with an average of 9.32±0.70. Observed heterozygosity (0.552±0.04) was less than the expected heterozygosity (0.648±0.035) pointing towards heterozygote deficiency in the population. In addition, positive value of FIS index (0.143±0.043) suggested considerable inbreeding. There was no indication of a recent bottleneck event in this population based on heterozygosity excess tests as well as mode-shift analysis. In summary, bovine microsatellite markers proved to be a valuable tool for characterization of Indian yak population. Arunachali yak represents an interesting gene pool with moderate level of diversity. Inbreeding in population calls for sincere efforts to formulate breeding policy so that this precious germplasm is conserved with substantial genetic diversity.